Importancia del big data en un gestor documental para las entidades públicas de Colombia (2021)
This article focuses on investigating how in public entities, archival electronic document management systems make it possible to identify whether big data contributes to meeting information management needs based on the analysis and interpretation of the evidence found. A qualitative exploratory methodology was used, based on a review of the subject literature. According to the results obtained, it may be concluded that in Colombia there is no project implementing big data in document managers to manage the information contained therein. The possibility of developing a tool for the analysis, recovery, organization, transformation, and agile and opportune storage of information is raised.